2016
DOI: 10.17344/acsi.2016.2297
|View full text |Cite
|
Sign up to set email alerts
|

Heteroannelation of Cyclic Ketones: Synthesis, Characterization and Antitumor Evaluation of Some Condensed Azine Derivatives

Abstract: A series of pyrimidine and thiazine derivatives was synthesized by one-pot reaction of cyclopentanone with a mixture of an aromatic aldehyde, namely o-anisaldehyde, and different ureas, namely urea, guanidine and thiourea, respectively. Furthermore, cycloaddition reaction of active methylene reagents, namely acetyl acetone, malononitrile, ethyl cyanoacetate, cyanoacetamide and N-phenyl cyanoacetamide with 2,6-bis(2-methoxybenzylidene)cyclohexanone afforded chromene and quinoline derivatives in basic medium. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Condensation reaction of compound 3 with some 1,3‐binucleophiles was investigated in different catalyzed reaction media. Reaction of thiourea with chalcone 3 can be either acid or base catalyzed . Treatment of an ethanolic solution of compund 3 with thiourea in the presence of catalytic amount of pipridine afforded pyrimidinethione derivative 6 in 85% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Condensation reaction of compound 3 with some 1,3‐binucleophiles was investigated in different catalyzed reaction media. Reaction of thiourea with chalcone 3 can be either acid or base catalyzed . Treatment of an ethanolic solution of compund 3 with thiourea in the presence of catalytic amount of pipridine afforded pyrimidinethione derivative 6 in 85% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Many of such compounds have shown relevant medicinal properties and have inspired the synthesis and investigation of the biological activities of a variety of compounds presenting a pyran ring as a structural feature, including 2-amine-4H-pyran-3-carbonitriles. A series of works have shown that 2-amine-4H-pyran-3-carbonitriles exhibit a broad spectrum of biological effects of pharmaceutical interest, such as anticancer, anti-microbial, antihemolytic, and antioxidant activities [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[31] Changes in their structure have offered a high degree of diversity that has proven useful for the development of new therapeutic agents having improved potency and lowered toxicity. Based on the above considerations and in continuation of our research on biologically potent heterocyclic derivatives, [32][33][34][35][36][37][38] herein, we report the synthesis, structural elucidation and antidiabetic activity of some new azoles and azines prepared from commercially available reagents.…”
Section: Introductionmentioning
confidence: 99%